Application of Legal Sanctions Against CSR Lawlessness by Limited Liability Companies - Anggriani Reni (E3S Web of Conferences)
The application of legal sanctions is one of the legal certainties for business actors is very important for business actors. Business actors involved in the implementation of the economy have a very important role in addition to the role of the state as a regulator or regulator is very important in the implementation of conducive economic development, because the state is a regulator or constitution maker in a country. Efforts to develop the community’s economy are through business. One of the business efforts carried out by legal entities that aim to obtain profits is a Limited Liability Company, which is regulated in Law Number 40 of 2007 concerning Limited Liability Companies. A Limited Liability Company in carrying out its business, not only thinks about the profits of a Limited Liability Company but must also pay attention to the surrounding environment. What are the legal sanctions against Limited Liability companies that do not carry out their obligations in carrying out their concern for the surrounding environment in providing CRS. This research was carried out normatively, using applicable laws and regulations. This study aims to find out how to apply legal sanctions to the social responsibility of a Limited Liability Company to the environment as regulated in the laws and regulations, namely Law Number 40 of 2007 concerning the Company and Government Regulation Number 47 of 2012, concerning Social and Environmental Responsibility of Limited Liability Companies.